Omalizumab in Reducing Exacerbation Rate and Oral Corticosteroid Burden in Allergic Bronchopulmonary Aspergillosis: A Systematic Review and Meta-Analysis - Harry Yuseptian; Fauzar; Roza Kurniati (Phlox Institute: Indonesian Medical Research Organization, 2026)
Background: Allergic bronchopulmonary aspergillosis (ABPA) is a hypersensitivity disorder complicating severe asthma and cystic fibrosis. Systemic corticosteroids, the mainstay of treatment, carry substantial cumulative toxicity, and the steroid-sparing role of the anti-IgE antibody omalizumab remains incompletely defined, particularly in South-East Asia where ABPA is under-recognised. Objective: To synthesise the most recent evidence on omalizumab for reducing exacerbations and oral corticosteroid (OCS) burden in adults with ABPA. Methods: Following PRISMA 2020, six databases were searched for original studies enrolling at least ten ABPA patients treated with omalizumab. Standardised mean differences (Hedges' g) were pooled using a DerSimonian–Laird random-effects model with the Hartung–Knapp–Sidik–Jonkman correction. Risk of bias, subgroup, sensitivity and meta-regression analyses, and GRADE certainty of evidence were assessed. Results: Ten studies (n = 286) were qualitatively synthesised; eight (n = 241) entered the quantitative pool. Omalizumab produced a moderate-to-large favourable composite effect (Hedges' g = −0.69; 95% CI −1.12 to −0.25; p = 0.007). Outcome-specific pooling confirmed reduced exacerbations (g = −0.74) and OCS dose (g = −0.81), and improved FEV1 (g = +0.48) and asthma control (g = +0.69) — about 1.9 fewer exacerbations per year and 9 mg/day prednisolone equivalent. Heterogeneity was substantial (I² = 78.4%) but robust across leave-one-out and sensitivity analyses. Conclusion: Omalizumab confers a clinically meaningful steroid-sparing benefit in adults with ABPA, supporting its adoption as maintenance therapy, pending adequately powered randomised trials in South-East Asian populations.